If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(8)(x + 4) + log(8)(x + 6) = log(8) * 24 Reorder the terms: glo * 8(4 + x) + log(8)(x + 6) = log(8) * 24 Reorder the terms for easier multiplication: 8glo(4 + x) + log(8)(x + 6) = log(8) * 24 (4 * 8glo + x * 8glo) + log(8)(x + 6) = log(8) * 24 (32glo + 8glox) + log(8)(x + 6) = log(8) * 24 Reorder the terms: 32glo + 8glox + glo * 8(6 + x) = log(8) * 24 Reorder the terms for easier multiplication: 32glo + 8glox + 8glo(6 + x) = log(8) * 24 32glo + 8glox + (6 * 8glo + x * 8glo) = log(8) * 24 32glo + 8glox + (48glo + 8glox) = log(8) * 24 Reorder the terms: 32glo + 48glo + 8glox + 8glox = log(8) * 24 Combine like terms: 32glo + 48glo = 80glo 80glo + 8glox + 8glox = log(8) * 24 Combine like terms: 8glox + 8glox = 16glox 80glo + 16glox = log(8) * 24 Reorder the terms for easier multiplication: 80glo + 16glox = 8 * 24glo Multiply 8 * 24 80glo + 16glox = 192glo Solving 80glo + 16glox = 192glo Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-192glo' to each side of the equation. 80glo + -192glo + 16glox = 192glo + -192glo Combine like terms: 80glo + -192glo = -112glo -112glo + 16glox = 192glo + -192glo Combine like terms: 192glo + -192glo = 0 -112glo + 16glox = 0 Factor out the Greatest Common Factor (GCF), '16glo'. 16glo(-7 + x) = 0 Ignore the factor 16.Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-7 + x)' equal to zero and attempt to solve: Simplifying -7 + x = 0 Solving -7 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + x = 0 + 7 x = 0 + 7 Combine like terms: 0 + 7 = 7 x = 7 Add '-1x' to each side of the equation. x + -1x = 7 + -1x Combine like terms: x + -1x = 0 0 = 7 + -1x Simplifying 0 = 7 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 6(w+5)=5w-4 | | 5x^2+14x-15=0 | | 48=10x^2-28x | | S-2=15 | | =te^13-4t | | 60+(5w)=m | | 9x-60=-6 | | -5y=10x+10 | | 56=17p-26 | | y=1.90+1.40t | | 8v+11=7v-20 | | 6x-14-2x=8x-9 | | 600+0.5(3000+0.05D)=D | | 8x+3-10=2(x-2)+3 | | -1k=287.658 | | 5(x-4)+2=42 | | 0.8b-1.2+2.3=12.2 | | 3.25n=52 | | 8=4sin(5x) | | 9-(4z-8)=1-5z | | 3.25n=53 | | 40-5c=55 | | 9(x-8)=7+8x | | S-2=25 | | 7x-8+2x=2+9x-9 | | 6x-13-3x=5x-6 | | 3.25n=54 | | Ln(9x+11)-Lynx= | | 12x+8=80 | | 12(x+9)=108 | | x^3-343=-0 | | -2(d-3d)=12 |